2020
DOI: 10.3390/app10124328
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of Micro-CT in Dentistry and Maxillofacial Surgery: A Literature Overview

Abstract: Micro-computed tomography (micro-CT) is a consolidated imaging technology allowing non-destructive three-dimensional (3D) qualitative and quantitative analysis by the observation of microstructures with high resolution. This paper aims at delivering a structured overview of literature about studies performed using micro-CT in dentistry and maxillofacial surgery (MFS) by analyzing the entire set of articles to portray the state of the art of the last ten years of scientific publications on the topic. It draws t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 134 publications
(174 reference statements)
0
19
0
Order By: Relevance
“…Design properties, powder quality, the setting up of process parameters and post-processing are some of the aspects that may affect the final quality and performance of the printed objects. In a context of regulated and critical products as the medical devices, the possibility to assess the achieved quality also at intermediate steps, Micro-CT analysis is considered as one of the major tools for the product quality assessment of AM products (Bibb et al, 2011;Campioni, Cacciotti et al, 2020;Campioni, Pecci et al, 2020;Center for Devices & Radiological Health, 2017). Micro-CT images showed that the hole dimensions and the shape were changed (coloured edges of some holes are evidenced in Figure 6); this kind of inaccuracy is present in all the specimens analysed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Design properties, powder quality, the setting up of process parameters and post-processing are some of the aspects that may affect the final quality and performance of the printed objects. In a context of regulated and critical products as the medical devices, the possibility to assess the achieved quality also at intermediate steps, Micro-CT analysis is considered as one of the major tools for the product quality assessment of AM products (Bibb et al, 2011;Campioni, Cacciotti et al, 2020;Campioni, Pecci et al, 2020;Center for Devices & Radiological Health, 2017). Micro-CT images showed that the hole dimensions and the shape were changed (coloured edges of some holes are evidenced in Figure 6); this kind of inaccuracy is present in all the specimens analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Micro‐CT analysis is considered as one of the major tools for the product quality assessment of AM products (Bibb et al, 2011; Campioni, Cacciotti et al, 2020; Campioni, Pecci et al, 2020; Center for Devices & Radiological Health, 2017). Micro‐CT images showed that the hole dimensions and the shape were changed (coloured edges of some holes are evidenced in Figure 6); this kind of inaccuracy is present in all the specimens analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations of micro-CT relate to the scanning and reconstruction processing time, the high costs of this technique, and the necessity of computer expertise. 1 10 The image file sizes are large (around 3 GB). As a result, data acquisition can be a problem when it is necessary to store and retrieve large volumes of files.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Micro-CT systems provide an opportunity to analyze microstructures, defects, and differences in density and morphology. Several types of samples - encompassing mineralized hard tissues, soft tissues, and solid or liquid materials - can be examined using micro-CT. 5 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation